Urogenital mycoplasma and its associations treatment option (clinical lecture) - A L Tikhomirov (IP Berlin A.V., 2013)
The azithromycin-containing Hemomycin and its compliance are discussed in this article. The use of this drug enhances compliance in the treatment of female genital organs inflammatory diseases.